CT and chest radiography in evaluation of mechanical circulatory support devices for acute heart failure - Abhishek Chaturvedi; Yonatan Rotman; Timothy Hoang; Greg Jew; Aniruddh Mandalapu; Craig Narins (Insights into Imaging, 2023)
Abstract Acute heart failure and cardiogenic shock are a major cause of morbidity and mortality in patients who have had recent cardiac surgery, myocardial infarct or pulmonary hypertension. The use of percutaneous mechanical circulatory support (MCS) devices before organ failure occurs can improve outcomes in these patients. Imaging plays a key role in identifying appropriate positioning of MCS devices for supporting ventricle function. These devices can be used for left ventricle, right ventricle or biventricular support. Fluoroscopy, angiography and echocardiography are used for implanting these devices. Radiographs and CT can identify both intra- and extra-cardiac complications. The cardiothoracic imager will see increasing use of these devices and familiarity with their normal appearance and complications is important. Critical relevance statement Chest radiographs and CT are useful for assessing the position of the mechanical cardiac support device used for treatment of acute heart failure. CT can identify cardiac and extra-cardiac complications associated with these devices. Graphical abstract Key points IABP upper/distal marker should be 2–3 cm distal to the ostia of the left subclavian artery. Inlet of Impella CP should be 3.5 cm below the aortic valve. The Impella 5.5 does not have a pigtail portion. The inlet should be about 5 cm below the aortic annulus. Impella RP inlet port should be in the right atrium or inferior vena cava, the pigtail portion should be positioned in the main pulmonary artery. Protek Duo inflow is in the right atrium or right ventricle. The outflow is in the main pulmonary artery.